Optimizing Rejected Oranges into Multipurpose Products in Seribu Jandi Village - Sofyan, Rudy; Ginting, Nurzainah; Masythah, Zuhrina; Ginting, Junita Setiana (Talenta Publisher, 2023)
One of the programs in the 8th Sustainable Development Goals (SDGs) is